Human Hemoglobin’s as Diagnostic Markers in the Conditions of the Republic of Karakalpakstan - Serimbetova Rufiya Saribayevna; Mambetullayeva Svetlana Mirzamuratovna (Zien Journals, 2023)
The article presents the results of the analysis of hemoglobin indicators in the blood of women living in the Republic of Karakalpakstan. It has been established that in all areas there is some "rejuvenation" of the process of hypo-hemoglobinosis, manifested at a fairly young age (30 years). The change in the ratio of blood hemoglobin types in clinical practice is used to diagnose various pathological conditions.
Keywords: Republic of Karakalpakstan; indicators; women; population health